STUDI KOMPARASI PRESTASI BELAJAR SISWA ANTARA SISWA YANG TINGGAL DI PONDOK PESANTREN DAN SISWA YANG TIDAK TINGGAL DI PONDOK PESANTREN - Salsabila, Humaira; Nalim, Yusuf (Dahzain Nur, 2024)
The purpose study find out the learning achievement students living in Islamic boarding schools, find out the learning achievement of students who do not live in Islamic boarding schools, find out the difference learning achievement between students living in boarding schools and students who live Islamic boarding schools. This study uses quantitativeapproach. The population in this study 170 students. Sampling used the Slovin formula, sthat sample of 62 students was obtained. The sampling technique used was proportionate stratified random sampling, that 15 students who lived in the cottage and 47 students live the cottage were obtained, (1) The learning achievement students living Islamic boarding schools the poor category, this evidenced by the results average test score, which is 68.8 in the interval of 57-69. (2) The learning achievement of students live in Islamic boarding schools the sufficient category, this is evidenced by the average test results, which 81.14 in theinterval of 70-82. (3) There significant difference between students who live Islamic boarding schools and students who Islamic boarding schools, this evidenced by the calculation the results of the t-test sampletest obtained with sig ( 2-tailed) 0.004 is less than 0.05, meaning it is rejected and accepted.????0????????